C-myc expression in adrenocortical tumours. Issue 2 (11th August 2017) - Pennanen, Mirkka; Hagström, Jaana; Heiskanen, Ilkka; Sane, Timo; Mustonen, Harri; Arola, Johanna; Haglund, Caj
Abstract : Aims: Widespread use of high-resolution imaging techniques and thus increased prevalence of adrenal lesions has made diagnostics of adrenocortical tumours an increasingly important clinical issue. In non-metastatic tumours, diagnosis is based on histology. New or enhanced information for clinicopathological diagnosis, revealing the malignant potential of the tumour, could emerge by means of biomarkers. The connection of proto-oncogene c-myc to adrenocortical neoplasias is poorly known, although the Wnt/beta-catenin pathway, one of the signalling pathways leading to induction of c-myc expression, has been connected to development of adrenocortical neoplasias. We studied c-myc expression in adrenocortical tumours and investigated molecules associated with the signalling pathway of c-myc, including cell cycle-related proteins p27, cyclin E and cyclin D1. Methods: We studied 195 consecutive adult patients with 197 primary adrenocortical tumours. Histopathological diagnosis was determined by Weiss score and the novel Helsinki score. C-myc, cyclin D1, cyclin E and p27 expressions were determined by immunohistochemistry. Results: Benign adenomas showed prominent nuclear c-myc expression comparable to that of normal adrenocortical cells, whereas carcinomas showed increased cytoplasmic expression. Strong cytoplasmic and weak nuclear c-myc expressions associated with malignancy and adverse outcome. C-myc staining did not correlate with cyclin E. Cyclin D1 correlated with cytoplasmic c-myc expression and to a lesser extent with nuclear c-myc. P27 correlated with cytoplasmic c-myc, but not with nuclear c-myc. P27 correlated with cyclin E. Conclusions: Strong cytoplasmic c-myc expression and weak nuclear expression in adrenocortical tumours associated with malignancy and shorter survival.